2001
DOI: 10.1038/sj.leu.2402139
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging detection of avascular necrosis of the bone in children receiving intensive prednisone therapy for acute lymphoblastic leukemia or non-Hodgkin lymphoma

Abstract: The purpose of this study was to determine the frequency with which magnetic resonance (MR) imaging detects avascular necrosis of the bone (AVNB) in children with acute lymphoblastic leukemia (ALL) or advanced-stage non-Hodgkin lymphoma (NHL) who receive prednisone during remission induction, reinduction, and maintenance chemotherapy; to assess the clinical significance of these findings; and to identify factors predictive of AVNB. We prospectively obtained MR imaging of the hips and knees of 116 children who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 30 publications
6
77
0
Order By: Relevance
“…8 As the earlier reports were based on retrospective data collection, the true osteonecrosis incidence was most likely underestimated. However, 6 of the 17 affected patients reported by Ribeiro et al 33 and 16 of the 23 patients reported by Niinimäki et al 8 were only detected by MRI, and the patients remained asymptomatic until the end of the study. Two independent retrospective reports on BerlinFrankfurt-Muenster (BFM)-based trials with quite similar therapy (AIEOP-ALL 95, 34 ALL-BFM 95 10 ) from the late 90s determined a much lower, but almost identical, osteonecrosis incidence of 1.6-1.8%.…”
Section: Osteonecrosis In the Context Of Anti-leukemic Treatmentmentioning
confidence: 77%
See 1 more Smart Citation
“…8 As the earlier reports were based on retrospective data collection, the true osteonecrosis incidence was most likely underestimated. However, 6 of the 17 affected patients reported by Ribeiro et al 33 and 16 of the 23 patients reported by Niinimäki et al 8 were only detected by MRI, and the patients remained asymptomatic until the end of the study. Two independent retrospective reports on BerlinFrankfurt-Muenster (BFM)-based trials with quite similar therapy (AIEOP-ALL 95, 34 ALL-BFM 95 10 ) from the late 90s determined a much lower, but almost identical, osteonecrosis incidence of 1.6-1.8%.…”
Section: Osteonecrosis In the Context Of Anti-leukemic Treatmentmentioning
confidence: 77%
“…A magnetic resonance imaging (MRI) screening based prospective study determined a significantly higher osteonecrosis incidence (15.5%) without the impact of steroid dose or dexamethasone administration (see Table 4). 33 This was even exceeded by a prospective study analyzing the Nordic ALL protocols, which reported an osteonecrosis incidence as high as 24%, identified by MRI screening at the end of treatment. 8 As the earlier reports were based on retrospective data collection, the true osteonecrosis incidence was most likely underestimated.…”
Section: Osteonecrosis In the Context Of Anti-leukemic Treatmentmentioning
confidence: 95%
“…For this study we aimed to investigate clinical relevant symptomatic ON. 17 Symptomatic ON was defined as persistent pain in the arms or legs not associated with recent vincristine administration, in combination with typical findings on magnetic resonance imaging(MRI). 18 Peripheral-blood samples were taken at diagnosis and at five time points (days 29, 33, 36, 40 and 43) during induction therapy of ALL (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…6,7 Correlation of imaging results with clinical symptoms such as pain, reduced mobility or immobilization is even more difficult in children. 8 Current treatment strategies aim primarily at elimination of pain, restoration of function and prevention of disease progression. Conservative measures are limited to immobilization and physiological rehabilitation, which is often complicated in children due to compliance problems.…”
Section: Introductionmentioning
confidence: 99%